Afro-Paradise : Blackness, Violence, and Performance in Brazil - Smith, Christen A., 1977- (University of Illinois Press, 2016)
Tourists exult in Bahia, Brazil, as a tropical paradise infused with the black population's one-of-a-kind vitality. But the alluring images of smiling black faces and dancing black bodies masks an ugly reality of anti-black authoritarian violence. This work argues that the dialectic of glorified representations of black bodies and subsequent state repression reinforces Brazil's racially hierarchal society.